Pemanfaatan Hasil Tangkap Ikan melalui Pelatihan Pembuatan Pempek di Kampung Rempang Cate - Oktavianto Gustin; Arif Roziqin; Sudra Irawan; Luthfiya Ratna Sari; Muhammad Zainuddin Lubis; Wenang Anurogo; Uuf Brajawidagda; Metta Santiputri; Nur Cahyono Kushardianto; Nur Zahrati Janah; Mir’atul Khusna Mufida; Yeni Rokhayati; Ari Wibowo; Satriya Bayu Aji; Fandy Neta; Rizki Widi Pratama; Anis Rahmi; Dwiki Novri Ditya; Rivki Ryan Nugraha (Pusat P2M Politeknik Negeri Batam, 2019)
The number of tourists and the fame of a long sand beach is still lacking, therefore it is necessary to introduce to the public about the beauty and marine products that are owned on Pasir Panjang beaches. This service community was carried out to socialize the benefits of marine products through training in making Pempek in the Pasir Panjang Coastal Village. We have carried out this service with the Partner of RW 03 Pasir Panjang, Pasir Panjang Village, Rempang Cate District on Friday, July 27, 2018. The questionnaire results of Speaker questionnaire with a Likert Scale, equipment and Room were found that the interpretation score from all observation was all worth 100% and include in the interval category very well, which meant that it was rated very well by 18 respondents. While for the consumption questionnaire the interpretation of the score of the observations is worth 95.556% and is included in the interval category Very Well which means it is rated very well by 18 Respondents. The results of monitoring on October 22, 2018 were obtained information that there were residents who had made Pempek and sold in Pasir Panjang environments, while production and sales had stopped due to constraints Limited fishing results. The results of the questionnaire obtained the most suggestions for further training to hold Crafts, other input so that the training activities continued. The results of the questionnaire obtained the most suggestions for further training is handicraft, other input so that the training activities continued.